Current issues of state regulation of psycho-social support in the conditions of war in Ukraine - Korolchuk, Olena; Zyma, Ivan; Khrapatyi, Sergii; Vikhliaiev, Mykhailo; Zavalko, Kateryna (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2023)
The relevance of this article is due to the fact that the existing approaches to ensuring the high quality of social protection and mental health care have not been implemented or are not effective. Despite the fact that the number of people who have suffered from a traumatic effect of the war has increased, there is no single integrated system for ensuring the protection of mental health in Ukraine. The purpose of the article is to develop a strategy for high-quality public management of psychosocial support for war victims in Ukraine. The results of the research show that the war increases the chance of acquiring mental health problems. So, the main issues of state regulation of psycho-social support are to create a system of psychosocial support and facilitate psycho-social recovery and create rehabilitation centers.